Intellectual Capital, Profitabilitas, Ukuran Perusahaan Dan Nilai Perusahaan - Aryanti, Ni Putu Intan; Mertha, Made (E-Jurnal Akuntansi; Vol 32 No 11 (2022)DO - 10.24843/EJA.2022.v32.i11.p11, 2022)
Increasing the value of the company is one of the goals of the company because by increasing the value of the company, the prosperity of shareholders will also increase. The research aims to obtain empirical data regarding the influence of intellectual capital, profitability and company size on firm value. The research was carried out at companies in the food and beverage sector that were listed on the Indonesia Stock Exchange in 2018-2020. A total of 17 companies were sampled using the nonprobability sampling method through a purposive sampling technique, resulting in 51 companies being sampled for 3 years. Multiple linear regression analysis was used as a data analysis technique. The output analysis reveals that profitability has a significant positive effect on firm value, but intellectual capital and firm size have a significant negative effect on firm value. Research provides implications in the form of considerations for investors when making decisions. This can be seen through research variables that can be used as corporate strategy and provide benefits to stakeholders. Keywords: Intellectual Capital; Profitability; Company Size; The Value of the Company